2021
DOI: 10.3390/photonics8110466
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Photonic Hooks from Patchy Microcylinders

Abstract: The photonic hook (PH) is a new type of curved light beam, which has promising applications in various fields such as nanoparticle manipulation, super-resolution imaging, and so forth. Herein, we proposed a new approach of utilizing patchy microcylinders for the generation of PHs. Numerical simulation based on the finite-difference time-domain method was used to investigate the field distribution characteristics of the PHs. By rotating the patchy microcylinder, PHs with different curvatures can be effectively … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Particles with an anisotropic refractive index distribution, such as Janus particles [17,18], are also suitable for the generation of PHs. In addition, PHs can be generated by partial or nonuniform illumination of symmetric and homogeneous particles [11,19], or by using dielectric particles partially covered with opaque films [20]. For example, Tang et al used 1 -35 µm diameter patchy microcylinders to generate PHs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particles with an anisotropic refractive index distribution, such as Janus particles [17,18], are also suitable for the generation of PHs. In addition, PHs can be generated by partial or nonuniform illumination of symmetric and homogeneous particles [11,19], or by using dielectric particles partially covered with opaque films [20]. For example, Tang et al used 1 -35 µm diameter patchy microcylinders to generate PHs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tang et al used 1 -35 µm diameter patchy microcylinders to generate PHs. Half of the cylinder surface is covered with silver films, and PHs with a bending angle of ∼ 28.4° can be generated under plane wave illumination [20].…”
Section: Introductionmentioning
confidence: 99%
“…Particles with an anisotropic refractive index distribution, such as Janus particles [18,19], are also suitable for the generation of PHs. In addition, PHs can be generated by partial or nonuniform illumination of symmetric and homogeneous particles [11,20], or by using dielectric particles partially covered with opaque films [21]. For example, Tang et al used 1 -35 µm diameter patchy microcylinders to generate PHs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tang et al used 1 -35 µm diameter patchy microcylinders to generate PHs. Half of the cylinder surface is covered with silver films, and PHs with a bending angle of ∼ 28.4 • can be generated under plane wave illumination [21].…”
Section: Introductionmentioning
confidence: 99%
“…3 In 2021, Tang et al theoretically investigated the influence of metal films on the generation of photonic hooks, and they found that the photonic hooks can be generated from patchy particle with a diameter between 1 µm to 35 µm. 4 Point source illumination can also be used to produce photonic hooks from patchy particles. 5 Here we reported the progress of using patchy particles for super-resolution imaging, and we showed that the performance of the imaging system can also be enhanced by coating microspheres with Al films.…”
Section: Introductionmentioning
confidence: 99%